2016
DOI: 10.36440/recmvz.v13i3.28823
|View full text |Cite
|
Sign up to set email alerts
|

Óbitos de cães e gatos durante procedimentos de banho e tosa: uma realidade pouco conhecida no Brasil

Abstract: Com o crescimento do mercado pet e suas inovações, proprietáriosde cães e gatos encontram cada vez mais alternativas paraa saúde e bem-estar de seus animais. Os estabelecimentos debanho e tosa vem ganhando espaço, uma vez que muitos proprietáriosnão dispõem de tempo e habilidade para a realizaçãoda higiene de seus animais. Porém, o que muitos proprietáriose até mesmo médicos veterinários desconhecem, é que cães egatos podem vir a óbito durante tais procedimentos aparentementeinofensivos, principalmente devido … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
1
0
1

Year Published

2021
2021
2021
2021

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 8 publications
1
1
0
1
Order By: Relevance
“…All cats (100%) were mixed breed. Similar data were found by Maria (14), who developed a retrospective study on the main changes found in autopsies of dogs and cats that died.…”
Section: Resultssupporting
confidence: 82%
See 1 more Smart Citation
“…All cats (100%) were mixed breed. Similar data were found by Maria (14), who developed a retrospective study on the main changes found in autopsies of dogs and cats that died.…”
Section: Resultssupporting
confidence: 82%
“…Dogs represent the majority of cases of animals received for the forensic necropsy. In the work developed by Marlet and (14), from 2003 to 2007, dogs also presented the highest percentage in all years of the study. However, dog and cat dynamics population has changed over the years, especially regarding cats population, which is increasing (8).…”
Section: Resultsmentioning
confidence: 88%
“…No mesmo sentido, estudo aponta: "Até mesmo um animal, frequentador assíduo de um pet shop, onde seja manipulado sempre pelo banhista e tosador habituais a cada visita, não estará livre de sofrer estresse" (MARIA; REGO; MAIORKA, 2015).…”
Section: Análise Envolvendo As Decisões Improcedentes De Primeira Instânciaunclassified